Diagnostic accuracy of f18-fluorodeoxyglucose positron emission tomography-computed tomography in the evaluation of carcinoma of unknown primary: A single-center study - Zahra, Umal Baneen; Younis, Muhammad Numair; Sheikh Danial Hanan,; Humaira Rauf,; Rimsha Badar,; Nefal Numair,; Abubaker Shahid, (Asian Journal of Medical Sciences, 2023)
Background: The term carcinoma of unknown primary (CUP) is not a single disease entity that it can be explicated as the recognition of metastasized tumor, in which the primary origin of the malignancy from an organ or site remains occult. The term refers to a clinical disorder that revolves around and represents a diversified metastatic tumor group, for whom the diagnostic investigations are unable to pinpoint the primary site of the tumor, comprising extensive radiological techniques, invasive endoscopic procedures, and histopathology, many which fail to diagnose the primary site. Aims and Objectives: The study was conducted to ascertain the diagnostic accuracy of fluorine-18 labeled fluorodeoxyglucose positron emission tomography-computed tomography (18F-FDG PET-CT) in the evaluation of CUP. The secondary objective of the study was to identify rate of the primary malignancies localized on 18F-FDG PET-CT that presents as CUP in local settings. Materials and Methods: The prospective and cross-sectional study included patients with CUP who underwent 18F-FDG PET-CT scans between October 2021 and February 2022. The primary site localized on 18F-FDG PET-CT was confirmed through biopsy and histology. False-negative and false-positive patients were ascertained through biopsy and/or follow-up of 6 months. Results: Of a total of 63 patients, 57.1% were male, while 42.9% were female with a mean age of 56.27 years. The overall detection rate of primary tumor (PT) site on 18F-FDG PET-CT was 88.8%. Abnormal sites and indicative of primary malignant tumor were correctly detected in 79.36% that were truly positive proven on biopsy. False-negative rate of scan was 4.76%, though malignancy was proven through other investigations or follow-up, while 6.36% had true negative and 9.52% showed false-positive results on the scan. In this study, the calculated diagnostic accuracy of 18F-FDG PET-CT identified as 85.7%, sensitivity 94%, specificity 40%, positive predictive value 89.2%, and negative predictive value 57.1%. Conclusion: 18F-FDG PET-CT demonstrated high sensitivity and diagnostic accuracy ascertaining the PT site in patients with CUP in our study population.